Use substitution to solve the system of equations.
[x = -3y – 13
(2x +2y = -6
A. (-28,5)
B. (2, -28)
C. (2, -5)
D. (11,-8)
Please select the best answer from the choices provided

Respuesta :

Answer:

(2, -5)

Step-by-step explanation:

x is defined by the first equation as x = -3y – 13.  Substitute  -3y – 13 for x in the second equation:

2( -3y – 13) + 2y = -6.

Performing the indicated multiplication, we get:

-6y - 26 + 2y = -6

Combining like terms results in:

-4y = 20, so that y = -5

Using the first equation, we find x for y = -5:

x = -3(-5) - 13 = 2

The solution is thus (2, -5) (Answer C)

C1042

Answer:

x=2 & y=-5, so the answer is C

Step-by-step explanation:

x = -3y-13 ------(1)

2x + 2y = -6 ---------(2)

sub(1)into(2)

(2)=> 2(-3y-13) + 2y = -6

-6y - 26 + 2y = -6

-4y = 20

y = -5

sub y=-5 into(1)

(1)=> x = -3(-5) - 13

= 15 - 13

= 2